Pengembangan Sistem Monitoring Truk Tangki Air berbasis Geographic Information System (GIS) pada PDAM Kota Malang - Fatimah Azzahra; Adam Hendra Brata; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Perusahaan Daerah Air Minum (PDAM) is a Regional Owned Enterprise in providing drinking water facilities for the community. Currently PDAM is making use of information and communication technology which is a process in realizing optimization of company performance so that it is faster, more precise, efficient and effective. PDAM Malang city provides clean, ready-to-drink water containing 4000Lt for free. The current process that must be carried out in ordering ready-to-drink clean water is by opening the Malang City PDAM Instagram which is found on the link, then customers can choose the Tugu Tirta Whatsapp which will be allocated to the Whatsapp number and can contact the PDAM to order clean water. However, there are difficulties on the part of PDAM in monitoring the delivery of tanker trucks that are carrying out the process of delivering water. So that a water tank truck monitoring system is needed using the Geographic Information System (GIS) method which will show the geographic location of the tanker truck delivery and can make it easier for customers to see the PDAM water delivery process. The system is made in the form of a website and android which produces the main features of monitoring introductions, submit a complaint and confirming deliveries. The system will be tested using whitebox testing, blackbox testing, and usability testing.